A New Cause of Obesity Syndrome Associated with a Mutation in the Carboxypeptidase Gene Detected in Three Siblings with Obesity, Intellectual Disability and Hypogonadotropic Hypogonadism - Asude Durmaz; Ayça Aykut; Tahir Atik; Samim Özen; Durdugül Ayyıldız Emecen; Aysun Ata; Esra Işık; Damla Gökşen; Özgür Çoğulu; Ferda Özkınay (Galenos Yayincilik, 2021)
Objective:Carboxypeptidase E (CPE) plays a critical role in the biosynthesis of peptide hormones and neuropeptides in the endocrine system and central nervous system. CPE knockout mice models exhibit disorders such as diabetes, hyperproinsulinaemia, low bone mineral density and neurodevelopmental disorders. Only one patient is described with morbid obesity, intellectual disability, abnormal glucose homeostasis and hypogonadotropic hypogonadism, which was associated with a homozygous frameshift deletion in CPE.Methods:Herein are described three siblings with obesity, intellectual disability and hypogonadotropic hypogonadism. Whole exome sequencing (WES) was performed in the index case. Candidate variants were prioritised and segregation of the variant, consistent with the phenotype of the index case, was assessed by Sanger sequencing in affected siblings and parents.Results:WES analysis revealed a homozygous nonsense c.405C>A (p.Y135*) mutation in CPE. Validation and segregation analysis confirmed the homozygous mutation in the index case and his affected siblings. The parents were phenotypically normal heterozygous mutation carriers.Conclusion:This study provides additional evidence of the association between a homozygous nonsense mutation in CPE and a clinical phenotype consisting of obesity, intellectual disability and hypogonadotropic hypogonadism, which may be considered as a new monogenic obesity syndrome.